2018
DOI: 10.21475/ajcs.18.12.12.p1230
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for anthracnose (Colletotrichum sublineolum Henn.) resistance in sorghum: challenges and opportunities

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is an important cereal crop grown for its diverse uses. Global sorghum production and productivity is affected by various stresses notably by biotic factors such as diseases, weeds and insect pests. Anthracnose caused by the fungal pathogen Colletotrichum sublineolum Henn. (formerly known as C. graminicola [Ces.] G.W. Wilson), grain mold, leaf blight, rust and smut are among the most import diseases of sorghum, while stem borer, shoot fly, termites and birds are notable pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Plants encounter various pathogens, such as bacteria, viruses, and fungi, which have caused crop yield loss globally [ 17 ]. Anthracnose disease in sorghum, generally caused by C. sublineola , brings great damage to the production of sorghum, especially for susceptible sorghum cultivars [ 10 , 15 ]. In this study, the role of sorghum EW in defending plants from anthracnose was determined in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants encounter various pathogens, such as bacteria, viruses, and fungi, which have caused crop yield loss globally [ 17 ]. Anthracnose disease in sorghum, generally caused by C. sublineola , brings great damage to the production of sorghum, especially for susceptible sorghum cultivars [ 10 , 15 ]. In this study, the role of sorghum EW in defending plants from anthracnose was determined in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, sorghum is one of the crops susceptible to C. sublineola. It was reported that anthracnose caused yield losses up to 67% in susceptible sorghum cultivars [ 15 ]. These results suggested that the high wax coverage on sorghum did not guarantee the sorghum disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…When sorghum anthracnose occurs, all tissues of sorghum can be infected. Therefore, without efficient disease management practices, the disease can devastate the whole crop [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases, such as stalk rot, downy mildew, grain mold, rust, head smut, leaf blight, and anthracnose are constraining global sorghum production (Wang et al, 2006;Little et al, 2012;Tesso et al, 2012;Das and Rajendrakumar, 2016;Mengistu et al, 2018). Because of its wide distribution and ability to infect all above ground parts of the plant, anthracnose caused by the destructive fungal pathogen Colletotrichum sublineola is one the most important diseases of sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…It is causing significant yield losses annually, especially in the tropical and subtropical regions where there are favorable climatic conditions for disease development (Erpelding, 2008). Yield losses of up to 67% due to anthracnose are recorded in susceptible sorghum cultivars (Mengistu et al, 2018) but, without efficient disease management practices, the pathogen can devastate the whole crop.…”
Section: Introductionmentioning
confidence: 99%